Gambaran Parent-Grandparent Co-Parenting Relationship pada Kakek-Nenek yang Mengasuh Balita - Rizki Agustin Purwaningtyas; Yuni Sufyanti Arief; Sri Utami (FORIKES, 2020)
Parental care by grandparents has become a worldwide phenomenon along with the increasing number of working mothers. Co-residing grandparent influence children’s growth and development, so good co-parenting is needed to avoid the negative impacts. This study aims to describe parent-grandparent co-parenting relationship in grandparents who provide child care because left by working mothers. The research method was descriptive survey and using simple random sampling technique with sample of 105 grandparents who provide child care because left by working mothers. Characteristics of grandparents 74.3% aged less than 60 years, 90.5% children raised by grandmothers. The majority of grandparents 99% came from Javanese ethnic and 55.2% had an elementary-junior high school education. As many as 87.6% respondents have an income less than IDR1,700,000.00/month and 60% mothers of children work as private employees. The results indicated that grandparents showed a good parent-grandparent co-parenting relationship in the role of childcare, which was marked by 65.7% co-parenting agreement good respondents, 73.3% co-parenting closeness of respondents good, 73.3% exposure of child to conflict respondents are good, 78.1% co-parenting support/undermining respondents are good, 85.7% endorsement of partner's parenting respondents are good, and only 58.1% of respondents perceive the division of labor in the sufficient category. The role of grandparents as children’s primary caregivers when left by working mothers will not interfere with attachment between parent-child if a harmonious parent-grandparent co-parenting relationship is created. Keywords: co-parenting; grandparenting; working mother ABSTRAK Pengasuhan balita oleh kakek-nenek menjadi fenomena yang mendunia seiring dengan meningkatnya jumlah ibu yang bekerja. Pengasuhan kakek-nenek berpengaruh terhadap pertumbuhan dan perkembangan balita, sehingga diperlukan co-parenting yang baik agar tidak terjadi dampak negatif. Penelitian ini bertujuan untuk mengetahui gambaran parent-grandparent coparenting relationship pada kakek-nenek yang mengasuh balita karena ditinggal ibu bekerja. Penelitian dilakukan menggunakan pendekatan survei deskriptif dan teknik pengambilan sampel yang digunakan yaitu simple random sampling dengan jumlah sampel 105 kakek-nenek yang mengasuh balita karena ditinggal ibu bekerja. Karakteristik kakek-nenek yang mengasuh balita 74,3% berusia kurang dari 60 tahun, 90,5% balita diasuh oleh neneknya. Mayoritas kakek-nenek 99% berasal dari Suku Jawa dan 55,2% berpendidikan SD-SMP. Sebanyak 87,6% responden mempunyai penghasilan kurang dari Rp1.700.000,00/bulan dan 60% ibu balita berkeja sebagai karyawan swasta. Hasil penelitian menunjukkan bahwa parent-grandparent co-parenting pada kakek-nenek yang mengasuh balita dalam kategori baik, yang ditandai dengan 65,7% co-parenting agreement responden baik, 73,3% co-parenting closeness responden baik, 73,3% exposure of child to conflict responden baik, 78,1% co-parenting support/undermining responden baik, 85,7% endorsement of partner’s parenting responden baik, dan hanya 58,1% responden yang mempersepsikan division of labor dalam kategori cukup. Peran kakek-nenek sebagai pengasuh utama balita ketika ditinggal ibu bekerja tidak akan mengganggu kelekatan antara orangtua-anak apabila tercipta parent-grandparent co-parenting relationship yang harmonis. Kata kunci: co-parenting; pengasuhan kakek-nenek; ibu bekerja